2020
DOI: 10.3390/jcm9061869
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Acute Hemoglobin Falls in Heart Failure Patients: A Population Study

Abstract: Aims: This study assessed the impact of acute hemoglobin (Hb) falls in heart failure (HF) patients. Methods: HF patients with repeated Hb values over time were included. Falls in Hb greater than 30% were considered to represent an acute episode of anemia and the risk of hospitalization and all-cause mortality after the first episode was assessed. Results: In total, 45,437 HF patients (54.9% female, mean age 74.3 years) during a follow-up average of 2.9 years were analyzed. A total of 2892 (6.4%) patients had o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
(32 reference statements)
0
1
0
Order By: Relevance
“…This indicates that mild anemia was less commonly recognized. Previous studies have shown that even minor anemia is associated with poor prognosis [ 30 , 31 ]. Therefore, clinicians should be careful in the recognition, assessment, and treatment of minor anemia.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that mild anemia was less commonly recognized. Previous studies have shown that even minor anemia is associated with poor prognosis [ 30 , 31 ]. Therefore, clinicians should be careful in the recognition, assessment, and treatment of minor anemia.…”
Section: Discussionmentioning
confidence: 99%